Sex‐specific effects of in vitro fertilization on adult metabolic outcomes and hepatic transcriptome and proteome in mouse. Issue 4 (18th March 2021) - Narapareddy, Laren; Rhon‐Calderon, Eric A.; Vrooman, Lisa A.; Baeza, Josue; Nguyen, Duy K.; Mesaros, Clementina; Lan, Yemin; Garcia, Benjamin A.; Schultz, Richard M.; Bartolomei, Marisa S.
Abstract: Although in vitro fertilization (IVF) is associated with adverse perinatal outcomes, there is increasing concern about the long‐term and sex‐specific health implications. Augmenting our IVF mouse model to longitudinally investigate metabolic outcomes in offspring from optimal neonatal litter sizes, we found sex‐specific metabolic outcomes in IVF offspring. IVF‐conceived females had higher body weight and cholesterol levels compared to naturally conceived females, whereas IVF‐conceived males had higher levels of triglycerides and insulin, and increased body fat composition. Through adult liver transcriptomics and proteomics, we identified sexually dimorphic dysregulation of the sterol regulatory element‐binding protein (SREBP) pathways that are associated with the sex‐specific phenotypes. We also found that global loss of DNA methylation in placenta was linked to higher cholesterol levels in IVF‐conceived females. Our findings indicate that IVF procedures have long‐lasting sex‐specific effects on metabolic health of offspring and lay the foundation to utilize the placenta as a predictor of long‐term outcomes.